The Untold History Of Pakistan’s Poultry Industry: A Review (Advances in Applied Biological Research, 2025)
Birth of Pakistan’s poultry industry is often attributed to the sole collaboration of  Pakistan’s International Air lines- PIA with that of Canada’s Messer Shaver’s Shaver  Breeding Farms. In this way, the role of the Government of Pakistan and Britian  Era’s Institutions, in the late 1940s, has been overlooked altogether. In addition, the  vital role played by worthy foreign and local investors e.g., Lever’s Brothers, Arber  Acres Private Limited, Packages Limited, has always been undermined while  unfolding the history of Pakistan poultry industry. This paper is a humble effort  to put some light on hidden gems of Pakistan’s poultry industry. By particularizing  their part in framing a strong poultry industry in Pakistan, it is an attempt to  express our appreciations towards these pioneers.
Keywords: Pakistan’s Poultry; King George V; history; PIA-Shaver; PPA; Punjab Veterinary School